The Effect Of The Problem Based Learning Model On Students' Mathematical Problem-Solving Abilities In Statistics Material In Grade VIII - Esra Margaretha Br. Pardosi; Efron Manik; Tutiarny Naibaho (Jurnal Pendidikan, Sains Sosial, dan Agama, 2020)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on students' mathematical problem-solving abilities in Statistics material for grade VIII. The method used is Quasi Experiment with a pretest-posttest control group design. The research sample consisted of two classes, namely the experimental class consisting of 31 students who were treated with the PBL model and the control class consisting of 28 students who were taught with the conventional model. The research instrument was a mathematical problem-solving test in the form of descriptions that had been tested for validity and reliability. The results showed that the N-Gain value in the experimental class was 0.73 (high category), while in the control class it was 0.32 (medium category). The average posttest score of students in the experimental class was also higher than that of the control class. Hypothesis testing using the t-test produced a t-value of 13.858 > t-table = 2.8 with sig. = 0.000 < 0.05, which means there is a significant influence of the PBL model on students' mathematical problem-solving abilities. Thus, the application of PBL can be used as an effective alternative in mathematics learning to improve students' problem-solving abilities.